2019
DOI: 10.1002/srin.201900084
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observation of Grain Refinement in the Simulated Heat‐Affected Zone of Al–Ti‐0.05% Ce‐Deoxidized Steel

Abstract: The particles and microstructural characteristics in the simulated heat‐affected zone (HAZ) of the Al–Ti deoxidized steel with 0.05% Ce treatment are investigated using in situ, optical, and electron microscopes and an electron backscattered diffraction analysis, and compared with the Al–Ti deoxidized steel with Ca treatment. The results reveal that the fine CeAlO3 inclusions and nanoscale (Ti, Nb)N precipitates are formed in the Ce‐bearing steel instead of the Ca–Al oxides surrounded by TiN and nanoscale (Ti,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Nowadays, in situ observation with high-temperature laser scanning confocal microscopy (HT-LSCM) has been utilized extensively to investigate the behavior of austenite grain growth during the thermal cycle of HAZ [25,26]. Wan et al [27] found that the growth process of austenite grains in Ti-micro-alloyed steel was a continuous process during heating, isothermal holding, and cooling in the simulated HAZ thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in situ observation with high-temperature laser scanning confocal microscopy (HT-LSCM) has been utilized extensively to investigate the behavior of austenite grain growth during the thermal cycle of HAZ [25,26]. Wan et al [27] found that the growth process of austenite grains in Ti-micro-alloyed steel was a continuous process during heating, isothermal holding, and cooling in the simulated HAZ thermal cycling.…”
Section: Introductionmentioning
confidence: 99%
“…The good combination of strength and toughness is usually associated with high density of the high‐angle grain boundary (HAGB) between the ferrite laths . The HAGB acts as obstacles to cleavage propagation and forces the cleavage crack to change the microscopic plane of propagation to accommodate the new local crystallography …”
Section: Resultsmentioning
confidence: 99%
“…The studies using RE to modify inclusions and improving steel microstructure and properties through the control of RE inclusions are also gradually increasing [7][8][9]. In addition, disperse high melting point RE inclusions are used to pin the austenite grain boundary and induce AF nucleation during the welding, which can also play the role in oxide metallurgy technology [10]. However, for high strength steel with high carbon equivalent, it is difficult to form AF, and easy to produce brittle structures such as upper bainite.…”
Section: Introductionmentioning
confidence: 99%